Growth, inter- and intraspecific variation, palaeobiogeography, taphonomy and systematics of the Cenozoic ghost shrimp Glypturus. (1st February 2016) - Klompmaker, Adiël A.; Hyžný, Matúš; Portell, Roger W.; Kowalewski, Michał
Abstract : Studies in systematic palaeontology are greatly aided when numerous, well-preserved specimens are available so that quantitative methods can be used to substantiate qualitative observations. This is often not the case for fossil decapod crustaceans due to their relatively low preservation potential. Here, we examined primarily two large collections of the well-preserved ghost shrimp Glypturus from the Holo-Pleistocene of Panama and the late Miocene of Florida. Using descriptive, bivariate, multivariate and geometric morphometric methods, two new species are described based on appendage material: Glypturus panamacanalensis sp. nov. and G. sikesi sp. nov. New characters are identified, and size-related and intraspecific variation are assessed for these taxa and modern G. acanthochirus . Taxonomic placement of single specimens from other localities was confirmed by multivariate methods. Furthermore, Glypturus is revised, especially with regard to Western Atlantic species that inhabited both carbonate and siliciclastic environments. Callianassa anguillensis, C. latidigata, and Neocallichirus? quisquellanus are referred to as Glypturus sp. until more material is available to determine the validity of these species. Diversity within Glypturus may thus be underestimated, thereby also impacting the assessment of phylogenetic relationships. Minor propodi appear under-represented relative to major propodi, suggesting a taphonomic bias. Single specimens of interest include a specimen of G. panamacanalensis sp. nov. exhibiting a peculiar swelling in the fixed finger and another showing damage on the propodal upper margin, suggesting failed predation or antagonistic behaviour. Glypturus is first found in the Oligocene in the Western Atlantic and may have expanded its palaeobiogeographical range since the Miocene. The genus was still present on the Pacific side of the Isthmus of Panama in the Holo-Pleistocene, but is only known from the Western Atlantic today, suggesting a relatively recent extinction on the Pacific side. http://zoobank.org/urn:lsid:zoobank.org:pub:C7F0C071-F2AD-4684-B277-037B6F91BF0E